ANALISIS SPASIAL: MELACAK TRANSFORMASI LAHAN GAMBUT DAN IMPLIKASINYA TERHADAP EKONOMI MASYARAKAT - Dian Wisnu Ajie Saputro; Indrawan Permana Kamis; Herwin Sutrisno (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to determine the condition of land use changes in peatlands. Where peatlands determine the resilience of Palangka Raya City through the level of vulnerability to disasters due to land and forest fires in peat conservation areas in the future. The literature review method was used in this research. The research results reveal that land resilience in Palangka Raya City, spatial and land planning factors need to be based on rational considerations in accordance with the existing potential of the area, so that there is efficient use of space without reducing land quality. Then, land conservation factors in Palangka Raya City are stipulated in spatial planning regulations which regulate the delineation and arrangement of cultivation areas and protected areas, developing protected areas as buffer zones, delineation and arrangement of agricultural areas. There are threats to land security in the form of flood disasters, rapid rates of urbanization or immigration, as well as various shocks and pressures, both caused by nature and humans. We need to be aware of this threat so that the peatland ecosystem in Palangka Raya City can be well maintained.